Strategi Korporasi Meningkatkan Jumlah Pelanggan Aplikasi Bimbingan Belajar Online di PT QLEVERS LABS Media Jakarta - Ridhowati Ridhowati (Sosio e-Kons, 2022)
The purpose of this study is to obtain information in the form of an explanation that corporate strategy can increase the number of customers and produce information from the results of the analysis about how much the corporate strategy can increase the number of customers. Qualitative research methods, research methods are based on the philosophy of post-positivism, which is used to examine a natural object that makes the researcher a key instrument. Data collection techniques through premier and secondary data. The results of the study are based on data obtained from the company regarding transactions that have occurred in 2016 – 2020, the number of sales and the number of Qlevers service customers has increased, which is characterized by a percentage of trends that have increased from the base year (2016). This is because the system readiness in the Qlevers application service began in late 2018. The target for 2025, the number of customers, and the number of sales are projected to increase from the previous year (2016 – 2020) with an average trend each year increasing by 71% for the number of customers and 69% for the number of sales. This indicates that companies must be ready to seize opportunities and increase their strengths, both in terms of application systems and in terms of service quality in order to compete with similar learning applications.